Economic Resilience in Tourism: Forecasting Financial Survival in Moroccan SME Hotels. - AHACHMI Mustapha; LAHFIDI Abdelhaq (African Scientific Journal, 2024)
Abstract Tourism significantly contributes to Morocco's economy, with SME hotels playing a crucial role in driving employment and economic activities. This study addresses the lack of targeted research on the financial stability of Moroccan SME hotels by developing a logistic regression model to predict financial distress. By analyzing 532 financial and operational data from these hotels, the research identifies key financial ratios such as debt-to-equity, liquidity, and profitability as vital predictors of bankruptcy (Zizi. Y, Oudgou. M., and El Moudden. A., 2020). The model provides high predictive accuracy, highlighting its practical application for preempting financial instability and enhancing risk management within the hotel industry. This research makes a significant contribution by focusing on an underexplored area, providing empirical evidence that supports the development of targeted financial strategies and policy interventions. It offers a specialized predictive tool that aids practical decision-making, thereby enhancing the resilience of a vital sector within Morocco's economy. The findings encourage further investigation into integrating more complex models and additional predictors to refine financial distress forecasts for SME hotels, ensuring their sustainability in varying economic conditions. Keywords: Firm Survival, Logistic Regression, Hotels, Morocco. Résumé Le tourisme contribue de manière significative à l'économie marocaine, les PME hôtelières jouant un rôle crucial dans la création d'emplois et d'activités économiques. Cette étude répond au manque de recherche ciblée sur la stabilité financière des PME hôtelières marocaines en développant un modèle de régression logistique pour prédire la détresse financière. En analysant 532 données financières et opérationnelles de ces hôtels, la recherche identifie des ratios financiers clés tels que le ratio dettes/capitaux propres, la liquidité et la rentabilité comme des prédicteurs essentiels de la faillite. Le modèle offre une grande précision prédictive, soulignant son application pratique pour prévenir l'instabilité financière et améliorer la gestion des risques dans l'industrie hôtelière. Cette recherche apporte une contribution significative en se concentrant sur un domaine sous-exploré, en fournissant des preuves empiriques qui soutiennent le développement de stratégies financières ciblées et d'interventions politiques. Elle offre un outil prédictif spécialisé qui aide à la prise de décision pratique, améliorant ainsi la résilience d'un secteur vital au sein de l'économie marocaine. Les résultats encouragent à poursuivre les recherches en intégrant des modèles plus complexes et des prédicteurs supplémentaires afin d'affiner les prévisions de détresse financière pour les PME hôtelières, garantissant ainsi leur durabilité dans des conditions économiques variables. Mots Clés : Survie Des Entreprises, Régression Logistique, Hôtels, Maroc